Not suicidal, just don’t want to live : A critical discourse analysis of the discursive construction of depression and suicidal ideation in the mental health community on Reddit - Shirley, Renee (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.